Strategi Komunikasi Humas Kementerian Sekretariat Negara dalam Mensosialisasikan KTT ke-43 ASEAN Plus Kepada Masyarakat Melalui Media Sosial - Pertiwi, Yolanda; Hartanto, Eko (Program Studi Ilmu Komunikasi Universitas Negeri Padang, 2023)
This research focuses on Public Relations of the Ministry of State Secretariat (Kemensetneg) in using communication strategies related to socializing the 43rd ASEAN Plus Summit to the public through social media. This research was conducted to identify and describe communication strategies and how the PR of the Ministry of State Secretariat overcomes the obstacles found. This study uses a descriptive qualitative approach with a case study methodology through in-depth interviews as a primary data collection method. This study uses the constructivism paradigm in viewing the problem. The theory used is the Agenda setting and the Concept of the Four Steps of Public Relations. The results of this study indicate that the Ministry of State Secretariat's Public Relations uses a communication strategy by applying the Agenda setting that has been determined and redeveloped by creating interesting and informative content before disseminating it through the Ministry of State Secretariat's social media. The designed communication strategy has also gone through several stages in accordance with public relations theory, namely the concept of the Four Steps of Public Relations by implementing four stages such as Fact Finding, Planning, Communication, and Evaluation. So that the Ministry of State Secretariat's Public Relations communication strategy in socializing the 43rd ASEAN Plus Summit to the public through social media can run well and be conveyed.